Classical Theories of Emotions: a 'Maintenance of Tradition' and an Aid for Understanding Current Debates (KULT_online, 2014)
Looking back on the manifold classical theories of emotions is indispensable for current discussions on emotions and emotionality. This aspect serves as the main thesis with which the editors of the anthology Handbuch Klassischer Emotionstheorien introduce the following articles. In this handbook, the thoughts and opinions of over 30 representatives of the Western philosophical tradition on emotions in general and specific emotions are portrayed. Despite some inaccuracies with regard to definitions, the anthology offers a comprehensive overview of the different characteristics of human emotions in the philosophical tradition.